Wing Polymorphism and Trypanosoma cruzi Infection in Wild, Peridomestic, and Domestic Collections of Mepraia spinolai (Hemiptera: Reduviidae) From Chile - Frias-Lasserre, Daniel; Gonzalez, Christian R.; Reyes Valenzuela, Carolina; Blanco de Carvalho, Danila [UNESP]; Oliveira, Jader [UNESP]; Canals, Mauricio; Aristeu da Rosa, Joao [UNESP] (Oxford Univ Press Inc, 2017)
Mepraia spinolai (Porter) is a vector of Trypanosoma cruzi that causes Chagas disease. Females are always wingless, but males may be winged or wingless. We determined by PCR the infection percentage with T. cruzi of M. spinolai adults and nymphs in domestic, peridomestic, and wild collections, in different regions of Chile. In all regions, winged males were more abundant than females and wingless males. Winged males collected inside houses were less parasitized than were those from peridomestic and wild environments. Although winged males of M. spinolai have comparatively low levels of infection, this segment may still represent the greatest vector threat in this species for transmission of T. cruzi to humans and other vertebrates in domestic, wild, and peridomestic habitats. Winged males represent the dispersive form of this species that invades human dwellings. Feeding deprivation resulting from the time required to find a food source and to search for reproductive females could explain the lower infection rates (negatives) of winged males collected from inside houses in comparison with winged males collected from peridomestic and wild habitats.
Keywords: Mepraia spinolai; Chagas disease; human dwelling; wing polymorphism